CMV hyperimmune globulin as salvage therapy for recurrent or refractory CMV infection in children undergoing hematopoietic stem cell transplantation - Panesso, Melissa; Uría, María Luz; Renedo, Berta; Esperalba, Juliana; Benítez-Carabante, María Isabel; Mendoza-Palomar, Natalia; Alonso, Laura; Oliveras, Maria; Diaz-de-Heredia, Cristina (Frontiers in Pediatrics, 2023)
Cytomegalovirus (CMV) is a major cause of allogeneic hematopoietic stem cell transplant (HSCT)related morbidity and mortality. In patients with CMV infection, treatment failure continues to be a major issue due to both drug resistance and intolerance. This single-center brief retrospective analysis of a case series aims to investigate the safety and efficacy of CMV-hyperimmune globulin as salvage therapy for CMV infection in children undergoing HSCT. Fifteen pediatric patients received human CMV-specific immunoglobulin (CMVIG) between July 2018 and December 2021 as a salvage therapy for refractory or recurrent CMV infection. At the time of CMVIG prescription, eight children presented with recurrent CMV infection and seven with refractory CMV infection. The overall response rate (ORR) was 67% at 50 days from the CMVIG administration [95% confidence interval (CI): 44-88]. Overall survival (OS) from CMVIG administration at 100 days was 87% [95% CI: 56-96], and OS from HSCT at 1 year was 80% [95% CI: 50-93]. In total four patients died, three deaths unrelated to CMV infection, and one due to CMV pneumonia. CMVIG as salvage therapy was well tolerated, and no infusion-related adverse events (AEs) were observed.